OP0034 The Serotonin Receptor 2 Inhibitor Terguride Has Beneficial Effects on Skin Fibrosis: Results from A Phase 2 Proof of Concept Study. (15th July 2016) - Distler, O.; Maurer, B.; Vettori, S.; Blumhardt, S.; Frey, D.; Distler, A.; Beyer, C.; Distler, J.H.
Abstract : Background: Circumstantial evidence from preclinical studies indicates a key role of serotonin (5-HT) signaling via the 5-HT-2B receptor in the development of fibrosis. Terguride is an orally available 5-HT-2 receptor inhibitor that has shown beneficial effects in different animal models of systemic sclerosis (SSc). Objectives: To evaluate the efficacy of Terguride for the treatment of fibrosis in patients with SSc in an investigator initiated phase 2 proof of concept study. Methods: Main inclusion criteria were fulfillment of ACR classification criteria and diffuse cutaneous SSc (dcSSc). Patients with end-stage organ involvement and treatment with potentially disease modifying agents including immunosuppressives were excluded. Patients were treated with Terguride at up to 3 mg/d p.o. or standard of care (post hoc control) for three months. Primary efficacy endpoints were changes of pre-defined skin biopsy biomarkers over the three months treatment period. Secondary efficacy endpoints included change of mRSS and lung function parameters. Serious adverse events (SAEs) and AEs were coded using MedDRA. The study was externally monitored. Results: Twelve patients were recruited into the Terguride group and 6 patients into the control group. The primary endpoints, skin biopsy biomarkers, showed a consistent and statistically significant down-regulation compared to the control group (Figure ) for dermal thickness, myofibroblast counts and mRNA levels of col1a1, col1a2 as well as for the Lafyatis 4-gene biomarker set (COMP, THSP-1, SIGLEC-1, IFI-44). This was accompanied by a reduction in mRSS of - 32.3% versus baseline in the Terguride group versus stable values in the control group (p<0.05). Lung function parameters did not change significantly. Overall, 33 AEs (n=27 mild and n=6 moderate) and one SAE (pyelonephritis, not related) occurred in the Terguride group, most often consisting of nausea and vomiting (9% and 13% of patients respectively).Twelve patients were recruited into the Terguride group and 6 patients into the control group. The primary endpoints, skin biopsy biomarkers, showed a consistent and statistically significant down-regulation compared to the control group (Figure ) for dermal thickness, myofibroblast counts and mRNA levels of col1a1, col1a2 as well as for the Lafyatis 4-gene biomarker set (COMP, THSP-1, SIGLEC-1, IFI-44). This was accompanied by a reduction in mRSS of - 32.3% versus baseline in the Terguride group versus stable values in the control group (p<0.05). Lung function parameters did not change significantly. Overall, 33 AEs (n=27 mild and n=6 moderate) and one SAE (pyelonephritis, not related) occurred in the Terguride group, most often consisting of nausea and vomiting (9% and 13% of patients respectively). Conclusions: Terguride was well tolerated in patients with dcSSc. Strong and consistent effects on fibrosis related skin biopsy biomarkers could be observed in this open-label controlled phase 2 proof of concept study, which was further supported by a significant improvement of the mRSS over the control group. These data justify further investigation in an upcoming randomized placebo controlled phase 3 study. Disclosure of Interest: O. Distler Grant/research support from: Bayer, Sanofi, Ergonex, Boehringer Ingelheim, Actelion, Pfizer, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, EpiPharm, Ergonex, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, MedImmune, Pharmacyclics, Pfizer, Serodapharm, Sinoxa, B. Maurer: None declared, S. Vettori: None declared, S. Blumhardt: None declared, D. Frey: None declared, A. Distler: None declared, C. Beyer: None declared, J. H. Distler Shareholder of: 4 D Science, Consultant for: Actelion, BMS, Celgene, Bayer Pharma, Boehringer Ingelheim, JB Therapeutics, Sanofi-Aventis, Novartis, UCB, GSK, Array Biopharma and Active Biotech